From Constitution to Conversation: Amazigh and the Delayed Dream of Full Recognition - Laaguid, Brahim Ait (Vivid: Journal of Language and Literature, 2025)
This study explores attitudes toward the Amazigh language among a diverse sample of 150 Moroccan participants, focusing on perceptions of its preservation, maintenance, and integration into public life. Data were collected through a structured questionnaire and analyzed using thematic analysis. The findings reveal overwhelmingly positive attitudes toward Amazigh, with the vast majority of respondents emphasizing the importance of preserving and maintaining the language. Most participants identified integration into priority domains of public life as the most effective strategy for achieving this goal. While many participants expressed great satisfaction with the constitutionalization of Amazigh, a notable proportion considered the step ineffective and inadequate, highlighting the lack of activation of its official status. These findings underscore the necessity of implementing tangible measures to elevate Amazigh's presence in Morocco’s sociopolitical and cultural landscape.